PEMAHAMAN KEIGO OLEH MAHASISWA PENDIDIKAN BAHASA JEPANG UNIVERSITAS RIAU ANGKATAN 2019 (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Keigo is a variety of respectful language used in Japanese and is one of the characteristics of the Japanese language. This study discusses the understanding of kenjougo among students of class 2019 of the Japanese Language Education Study Program, FKIP, Riau University. The purpose of this study was to find out how the understanding of kenjougo in class 2019 students was. The method used in this study was descriptive quantitative. The results of this study indicate that the understanding of the 2019 batch of students towards kenjougo is in the low category. This is due to the lack of students' understanding of the function and form of kenjougo. In addition, the time period for receiving material regarding keigo material with the research time is quite far so it can be concluded that students have limitations in remembering the material.Key Words: Understanding, Keigo, Kenjougo